2013
DOI: 10.3174/ajnr.a3707
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Endovascular Treatment for Acute Stroke in the SWIFT Trial with Solitaire and Merci Devices

Abstract: BACKGROUND AND PURPOSE: Treatment of patients with ischemic stroke after endovascular treatment requires in-depth knowledge of complications. The goal of this study was to make endovascular treatment for acute ischemic stroke safer through an in-depth review of the major periprocedural complications observed in the Solitaire FR With Intention for Thrombectomy (SWIFT) trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 20 publications
2
81
0
2
Order By: Relevance
“…intra-arterial thrombolysis, MT or both) [5]. In the SWIFT trial, ID was observed in 5 (3.5%) of the 144 patients treated with MT (Merci ® and Solitaire ® devices) [16]. These numbers are in line with the ID frequency of 2% (18/866) overall and 3.4% (18/524) seen in MT patients in our study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…intra-arterial thrombolysis, MT or both) [5]. In the SWIFT trial, ID was observed in 5 (3.5%) of the 144 patients treated with MT (Merci ® and Solitaire ® devices) [16]. These numbers are in line with the ID frequency of 2% (18/866) overall and 3.4% (18/524) seen in MT patients in our study.…”
Section: Discussionsupporting
confidence: 88%
“…The ID did not have a significant impact on clinical outcome compared to patients without ID despite severe complications possibly related to ID in 2 patients. To date, arterial dissection as a complication of endovascular AIS treatment has been systematically reported by the MR CLEAN, REVASCAT, SWIFT and STAR investigators [5,9,16,17]. Dissection occurred in 1% of STAR patients and 3.9% of REVASCAT patients as a complication of AIS treatment with either Solitaire ® (Medtronic, Dublin, Ireland) flow restoration thrombectomy or combined with medical management alone [9,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These included 5 patients treated for MCA M1 occlusion; 3, for ICAT occlusion; and 2, for ICA tandem occlusion, which overall represented 4.3% of all patients undergoing anterior circulation MT procedures during the analyzed time (see above). The median baseline NIHSS score was 16 (interquartile range, [13][14][15][16][17][18][19], and the median time from symptom onset to the start of the MT procedure was 168 minutes (interquartile range, 150 -179 minutes). For both ICA tandem occlusions, proximal ICA stent placement was performed before MT.…”
Section: Resultsmentioning
confidence: 99%